Formalization of Linear Space Theory in the Higher-Order Logic Proving System - Jie Zhang; Danwen Mao; Yong Guan (Journal of Applied Mathematics)
Theorem proving is an important approach in formal verification. Higher-order logic is a form of predicate logic that is distinguished from first-order logic by additional quantifiers and stronger semantics. Higher-order logic is more expressive. This paper presents the formalization of the linear space theory in HOL4. A set of properties is characterized in HOL4. This result is used to build the underpinnings for the application of higher-order logic in a wider spectrum of engineering applications.